“Hey Sam” Creando con autismo (2024)
Play in early childhood is not just an activity recreational, but also triggers processes fundamental in the cognitive, emotional and social development of the children. Through play, they explore the world around them. surroundings, they test their senses and increase the skills necessary for comprehensive development.